INSTRUMEN PENELITIAN DAN URGENSINYA DALAM PENELITIAN KUANTITATIF - Hamni Fadlilah Nasution (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
Allah gave every people the ability to think. The ability to think used to be able to find the best for as the solution of the problems of life is experienced, the solution is often called the study results. From use the provision of procedures carried out in accordance with the steps of scientific thinking. Data are urgent matters in the research. Data is the lifeblood of research. One way to obtain research data is to provide instruments that correspond to the variables to be studied. Instrument can be given a test and non test. Instruments in the study must meet the criteria of reliability. The goal for the instrument given to the respondents is the right instrument to measure the variables of research based on the indicators of the instrument.